Penerapan Metode Belajar Interaksi Sosial oleh Kader pada Pencapaian ASI Ekslusif 1 - Umami, Riza; Restanti, Dian Aby (POLTEKKES KEMENKES MANADO, 2022)
Background: Posyandu is a community-based health effort driven by selected cadres to carry out routine Posyandu activities as reform agents who act as community mobilizers, counseling and monitoring related to the success of achieving exclusive breastfeeding. The success of exclusive breastfeeding includes E1 to E6 status, but in practice, there are obstacles experienced by cadres in carrying out their duties because the level of education is still lacking and they have not received training. Purpose: this study was to examine the application of social interaction learning models by cadres in achievement of exclusive breastfeeding status 1. Method: this study uses a correlational method. Results: the study showed that there were differences in the level of knowledge of Cadres before and after mentoring p-value = 0.010, achievement of E1 Status was 78% (28 people) and the application of social interaction learning models by Cadres was only 33% (24 people) then the data was analyzed using chi square, while the p-value = 0.777. which means that there is no relationship between the application of the social interaction learning model and the attainment of Exclusive ASI status 1. It can be assumed that there are factors that influence a person's knowledge including age, level of education, occupation, interests, and sources of information.